The Relationship between Work Stress and Fatigue and Sleep Quality in Speech Therapist Health Personnel in Medan City, Indonesia - Prasetyo, Aditya Anggren; Hastuti, Lis Sarwi (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Work is one of the activities carried out by a speech therapist in order to meet daily needs and desires for something. During the work process, speech therapists often experience obstacles that develop into negative feelings in the form of work stress and fatigue at work. The demands of the speech therapist's work environment can result in changing sleep patterns so that the speech therapist has poor sleep quality. Objectives: This study aims to determine the relationship between work stress and fatigue and sleep quality in speech therapist health workers in the city of Medan. Methods: This type of research is a non-experimental quantitative with a cross-sectional approach. The sampling technique used was purposive sampling with 28 speech therapists as respondents. Measurement of work stress using the Perceived Stress Scale questionnaire (PSS-10), fatigue measurement using the Industrial Fatigue Research Committee (IFRC) questionnaire and measurement of sleep quality using the Pittsburgh Sleep Quality questionnaire (PSQI). Data analysis was performed using the SPSS version 25.0 statistical program using the Spearman Rank statistical test. Results: The majority of respondents aged 20-40 years (82.1%), female (75%), married (57.1%), Diploma III education level (92.9%), working period 1-10 years (75 %). Speech therapists experienced moderate stress (53.6%) with low fatigue (64.33%) and good sleep quality (60.7%). The results of the correlation test obtained a value of r=0.192 (p=0.000) for the fatigue variable and a value of r=0.211 (p=0.000) for the sleep quality variable. Conclusion: There is no correlation between work stress and fatigue and work stress and sleep quality among speech therapist health workers in Medan City. Bibliography: 16 (2012-2021) Keywords: Speech Therapist, Job Stress, Fatigue, Sleep Quality.